Differential relationship between meditation methods and psychotic-like and mystical experiences. - Timothy Palmer; Kenza Kadri; Eric Fakra; Jacqueline Scholl; Elsa Fouragnan (PLoS ONE)
Much work has investigated beneficial effects of mindfulness-based meditation methods, but less work has investigated potential risks and differences across meditation methods. We addressed this in a large pre-registered online survey including 613 mediators where we correlated participants' experience with fifty meditation techniques to psychotic-like experiences (PLEs) and mystical experiences. We found a positive correlation for both PLEs and mystical experiences with techniques aiming at reducing phenomenological content ('null-directed', NDM) or classified as non-dual or less embodied. In contrast, methods aiming at achieving an enhanced cognitive state (CDM), also described as 'attentional' or strongly embodied, showed negative correlations with PLEs. Interestingly, participants' subjectively perceived that all types of meditation techniques were preventative of PLEs but less so for NDM. Participants differed in their reasons for meditating, broadly grouped into associated with spiritual exploration and associated with health. Participants who meditated for spiritual reasons were more likely to choose NDM techniques and more likely to experience PLEs. In contrast, participants who meditated for health-related reasons were more likely to choose CDM techniques. This study provides important information for meditators about the relationship of different techniques with PLEs and the moderating influences of individual traits.